2014
DOI: 10.1007/s12328-014-0510-6
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-directed thrombolysis through the operatively recanalized umbilical vein for acute extensive portal vein thrombosis: report of a case

Abstract: Acute portal vein thrombosis is a rare but severe complication of intra-abdominal infection. It can be life-threatening, given the risk of developing liver abscess and subsequent liver failure. Various types of hereditary thrombophilia are known risk factors for acute portal vein thrombosis. In addition to surgical treatment and potent antibiotic therapy, systemic administration of anticoagulants and locoregional trans-catheter delivery of thrombolytic agents are known to be effective. We present a case report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Articles published in languages other than English; cases where clinical, microbiological, or radiological studies did not support the diagnosis; case reports not providing an adequate amount of information, as well as those reporting non-human subjects were excluded from the analyses. The final number of articles included was 101, which resulted in total number of 103 patients [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ,…”
Section: Methodsmentioning
confidence: 99%
“…Articles published in languages other than English; cases where clinical, microbiological, or radiological studies did not support the diagnosis; case reports not providing an adequate amount of information, as well as those reporting non-human subjects were excluded from the analyses. The final number of articles included was 101, which resulted in total number of 103 patients [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ,…”
Section: Methodsmentioning
confidence: 99%
“…In a case report by Sherigar et al, 17 the progression of thrombus and portal hypertension can be prevented by the use of thrombolytics. Tamaki et al 18 have shown a rapid resolution of symptoms with thrombolytics and concluded that appropriate antibiotics, along with local thrombolytic therapy, improve patient outcomes. In a retrospective study, Naymagon et al 19 treated their patients with intravenous heparin and were later transitioned to enoxaparin, warfarin, or direct oral anticoagulants after stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…2 One case study used the surgically recanalized umbilical vein for thrombolytic access because of the inability to use the splanchnic veins for fear of overwhelming intra-abdominal contamination from perforated appendicitis. 3 Treatment of portal vein thrombosis in cirrhosis with infusion of thrombolytics into the superior mesenteric artery has also been established as a treatment option to recanalize the portal system. 4 Catheter-directed thrombolysis has been described as a method of treating thrombosis of the SMV and portal vein.…”
Section: Discussionmentioning
confidence: 99%